CULTUREN VALUE EDUCATION IN SCHOOLS - Doga Emine (Sensei International Journal of Education and Linguistic, 2021)
Values-oriented education today is urgently needed in order to develop and strengthen the noble character of humanity in the midst of concerns about social phenomena lately which have been very troubling. The purpose of this research is to cultivate values education in schools as the core of the learning process and objectives. The method used in this research is descriptive method, namely the researcher's attempt to solve the actual problem (up to date) by collecting data, compiling or classifying it, analyzing it, and interpreting it. As for data collection techniques using library research (library research) where researchers collect data by reading, studying, and analyzing journals, books, articles from previous researchers.